Pemanfaatan puntung rokok dan serai untuk pembuatan biopestisida dalam mengendalikan hama tanaman di Desa Katumbangan Lemo: Utilization of cigarette butts and Lemongrass on Biopesticide Production for pest handling in Katumbangan Lemo Village - Isdaryanti Isdaryanti; Alexander Kurniawan Sariyanto Putera; Muhammad Rizal Kurniawan Yunus; Sufyan Hakim; Nursyamsi SY.; Muhammad Arhim (Agriculture and Forestry Faculty, Universitas Sulawesi Barat, 2024)
Plant pests are one of the challenges faced by farmers. These pests are difficult to eradicate and increase production costs due to the many pesticides used. Therefore, this community service program introduced practical and affordable biopesticides. The program was conducted in two sessions, with session 1 being a lecture session and session 2 involving hands-on practice. The methods employed in this program included lectures, training, and discussions. In session 1, 20 participants attended, while session 2 saw an increase to 40 participants. The training covered theoretical materials on the basics of biopesticides, the ingredients, procedures, and mechanisms of action. The practical session involved the biopesticide-making process, which consisted of 6-8% cigarette butts, 25% lemongrass, 10% sugar, 20% EM4, and 1 liter of water. Based on the evaluation results before and after the activity, it was found that all evaluation indicators showed significant improvements in terms of knowledge, skills, interest, and practicality. Therefore, this program has successfully enhanced the participants’ knowledge, skills, and interest in applying biopesticide production in their daily work.